The First Graduate of Dental Medicine at the University of Zagreb - Dumančić, Jelena (Acta Stomatol Croat, 2018)
Dentistry in Croatia started as a course Dentistry and Dental Medicine for medical students at the School of Medicine in Zagreb in 1922. The first teacher was Professor Eduard Radošević, doctor of medicine and dentistry specialist. The next stage was formation of the Odontology Department at the School of Medicine in Zagreb in September 1948, which was supported by Professor Ivo Čupar. The first 47 students enrolled in dentistry. Milenko Lainović was the first student who graduated from the School on May 26, 1954 and he received the title of a graduated doctor of dental medicine. He was the first doctor of dental medicine in the history of the University of Zagreb. Following graduation, Dr. Lainović returned to his native town Podgorica in Montenegro. He reorganized the dental service in Montenegro and founded the Secondary School for Dentists, Technicians, Sanitary Technicians and Medical Laboratory Technicians. He specialized in oral surgery in 1969, and in 1971 he founded a dental section at the Society of Physicians of Montenegro. Also, he was the initiator and organizer of several scientific and expert meetings in Montenegro. Dr. Lainović was awarded the title of primarius and his busy career lasted 58 years. Numerous awards and prizes have witnessed the contribution of Primarius Dr. Lainović to dental development in Montenegro and Yugoslavia. We are grateful to Primarius Dr. Lainovic for the promotion and affirmation of dental profession and the School of Dental Medicine, as well as for collecting numerous data on the development of dental profession, which are precious documents of history. This paper is dedicated to Primarius Dr. Lainović on the occasion of the 70th Anniversary of Dentistry at the University of Zagreb (1948-2018).